Endothelial microparticles: A mechanosensitive regulator of vascular homeostasis and injury under shear stress - Feng, Shuo; Chen, Jia Wei; Shu, Xin Yi; Aihemaiti, Muladili; Quan, Jin Wei; Lu, Lin; Zhang, Rui Yan; Yang, Chen Die; Wang, Xiao Qun (Frontiers in Cell and Developmental Biology, 2022)
Hemodynamic shear stress (SS), a frictional force generated by blood flow, regulates vascular homeostasis. High and steady SS maintains physiological function of endothelial cells while low and disturbed SS promotes disturbance of vascular homeostasis and the development of atherosclerosis. Endothelial microparticle (EMP), a vesicular structure shed from endothelial cells, has emerged as a surrogate biomarker of endothelial injury and dysfunction. EMP release is triggered by disturbed SS in addition to multiple inflammatory cytokines. This review systematically summarizes the impact of SS on EMPs and the role of EMPs under SS in modulating vascular homeostasis and injury, including endothelial survival, vasodilation, inflammatory response, vascular permeability, and coagulation system.